Antiproton Physics - Richard, Jean-Marc (Frontiers in Physics, 2020)
We review the physics of low-energy antiprotons, and its link with the nuclear forces. This includes: antinucleon scattering on nucleons and nuclei, antiprotonic atoms and antinucleon-nucleon annihilation into mesons.